Comparison of Open-Source Distributed Computing Framework for Big Data - Ai Fang; Xiong Xu; Bing Liang; Yuzhong Zhang; Yiping Yang (Dianxin kexue)
A comparison of three open source distributed computing frameworks for big data （Hive，Impala and Spark）was conducted.Tests were run to evaluate the performance aiming at real business demands.The cost of implementation to meet business requirements was also discussed.